THE CONCEPT OF PUBLIC SECURITY NATIONAL AND FOREIGN ANALYSIS (World Bulletin of Management and Law, 2022)
This article aims to further clarify the concept of public security. A thorough study of most of the national literature related to public security revealed that there is no single approach to the concept of "public security". In the main legal document in public security activities, namely Decree No. PF-27, adopted on November 29, 2021, "On approval of the concept of public security of the Republic of Uzbekistan and measures for its implementation", it is stated that "Public security - illegal aggression of society, social and ethnic conflicts, it is a state of protection from emergency situations and other threats, which serves the sustainable development of society and ensures the realization of human rights, freedoms and legitimate interests. However, if we analyze the Western experience, we can see that there is a slight difference from the above concept in the disclosure of the essence of public security. In this regard, in this article, during the study of national and foreign literature, the ideas related to the concept of public security will be more clearly analyzed